Structural quality of antenatal clinics in the public health sector in a Northern district in Kerala, India - Mundodan, Jesha Mohammedali (International Journal Of Community Medicine And Public Health, 2017)
Background: To achieve the 5th Millennium Development Goal countries throughout the world are investing more energy and resources in providing equitable, adequate maternal health services. Objectives of the study was to assess the quality of structural attributes in the antenatal clinics in public health sector. Methods:A cross sectional study was conducted in 30% of the institutions at various levels in the public health sector in Kozhikode district during September to February 2010-11. Structural quality was assessed using a checklist. A 3-point score was used. Mean score was used for comparing between different levels. The actual score for each attribute was calculated as percentage of maximum total and standard of 60 % was taken as cut off to categorize facilities as good or poor. Results: Out of the 28 institutions studied, 12 had good score for structural attributes. Attributes like general infrastructure, availability of basic diagnostic equipments and maintenance and cleanliness of health facility scored well at all levels. General Infrastructure was found to be good in 23 health facilities; maintenance was good in 17 facilities and 19 facilities scored well for Basic Diagnostic Equipments. Basic Laboratory Facilities was grossly inadequate in all institutions especially at the PHC level. Only 8 facilities had Adequate Drugs Supply. The overall score for all the structural attributes (p 0.008) was found to be significantly different between the various levels of public health sector with good scores at MCH, TH and BPHC level and difference in scores was found to be significant with regards to availability of Basic Laboratory Services (p 0.032); Basic Diagnostic Equipments (p 0.031) and availability of drugs (p 0.005). Conclusions:Further improvement in this regard is necessary in the PHCs, BPHCs and CHCs.